2017
DOI: 10.1038/s41533-016-0005-7
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Salzburg COPD-screening questionnaire (SCSQ): a questionnaire development and validation study

Abstract: Chronic obstructive pulmonary disease prevalence rates are still high. However, the majority of subjects are not diagnosed. Strategies have to be implemented to overcome the problem of under-diagnosis. Questionnaires could be used to pre-select subjects for spirometry and thereby help reducing under-diagnosis. We report a brief, simple, self-administrable and validated chronic obstructive pulmonary disease questionnaire to increase the pre-test probability for chronic obstructive pulmonary disease diagnosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“… 40–42 For example, an AUC-ROC of 0.66 was reported in a study that assessed the predictive value of the Salzburg-COPD screening questionnaire for use in a primary care setting. 42 Thus, in Japan, the CAPTURE and COPD-Q may be useful to identify symptomatic COPD, but further spirometry assessment would be needed to confirm a diagnosis. Individuals with high scores on these screening questionnaires should undergo spirometry testing, to support early diagnosis, access to preventive care, and/or appropriate COPD treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 40–42 For example, an AUC-ROC of 0.66 was reported in a study that assessed the predictive value of the Salzburg-COPD screening questionnaire for use in a primary care setting. 42 Thus, in Japan, the CAPTURE and COPD-Q may be useful to identify symptomatic COPD, but further spirometry assessment would be needed to confirm a diagnosis. Individuals with high scores on these screening questionnaires should undergo spirometry testing, to support early diagnosis, access to preventive care, and/or appropriate COPD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…8 In contrast, the CAT questionnaire can be completed by the subject him/her self before the medical examination. Various questionnaires that screen for COPD in the general population have been developed, [9][10][11] but the advantage of the CAT questionnaire is its dual screening and monitoring function, which enables patients to be followed-up.…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous studies have suggested using self-administered questionnaires to screen for COPD. [9][10][11] The COPD Assessment Test (CAT) was initially developed and validated for routinely assessing and monitoring COPD patients. 12,13 It was later used to help screen for COPD in both smokers, 14,15 and the general population.…”
Section: Introductionmentioning
confidence: 99%
“…[81] Several other diagnostic tools have been developed to detect clinically significant COPD, and various screening surveys have been launched. [82][83][84][85][86] While these instruments are often user-friendly for patients, their administration should be approached cautiously, considering their limitations. Their moderate accuracy and inability to differentiate between stages of obstruction underscore the necessity of using them in conjunction with spirometry.…”
Section: Current Challenges and Opportunitiesmentioning
confidence: 99%